LAMIUM L. IN THE GAREEV GARDEN OF NAS KR (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article provides information about plants of the genus Lamium L., introduced in the Gareev Botanical Garden of NAS KR. Their brief botanical description, phenology and methods of reproduction in garden conditions, use in landscaping as ground covers are given.
Keywords: collection, introduction, phenology, ground cover plants, Lamium, planting of greenery.